A Risk Stratification Model for Predicting Overall Survival and Surgical Benefit in Triple-Negative Breast Cancer Patients With de novo Distant Metastasis - Wang, Zheng; Wang, Hui; Sun, Xi; Fang, Yan; Lu, Shuang-Shuang; Ding, Shu-Ning; Chen, Xiao-Song; Shen, Kun-Wei (Frontiers in Oncology, 2020)
Background and aims: This research aimed to construct a novel model for predicting overall survival and surgical benefit in triple-negative breast cancer (TNBC) patients with de novo distant metastasis. Methods: We collected data from the SEER database for TNBC patients with distant metastasis between 2010 and 2016. Patients were excluded if the data regarding metastatic status, follow-up time or clinicopathological information were incomplete. Univariate and multivariate analyses were applied to identify significant prognostic parameters. By integrating these variables, a predictive nomogram and risk stratification model were constructed and assessed with C-indexes and calibration curves. Results: A total of 1737 patients were finally identified. Patients enrolled from 2010-2014 were randomly assigned to two cohorts, 918 patients in the training cohort and 306 patients in the validation cohort I, and 513 patients enrolled from 2015-2016 were assigned to validation cohort II. Seven clinicopathological factors were included as prognostic variables in the nomogram: age, marital status, T stage, bone metastasis, brain metastasis, liver metastasis and lung metastasis. The C-indexes were 0.72 in the training cohort, 0.71 in validation cohort I and 0.71 in validation cohort II. Calibration plots indicated that the nomogram-based predictive outcome had good consistency with the recoded prognosis. A risk stratification model was further generated to accurately differentiate patients into three prognostic groups. In all cohorts, the median overall survival time in the low-, intermediate- and high-risk groups was 17.0 months (95% CI 15.6-18.4), 11.0 months (95% CI 10.0-12.0), and 6.0 months (95% CI 4.7-7.3), respectively. Locoregional surgery improved prognosis in both the low-risk (HR 0.49, 95% CI 0.41-0.60, P<0.0001) and intermediate-risk groups (HR 0.55, 95% CI 0.46-0.67, P<0.0001), but not in high-risk group (HR 0.73, 95% CI 0.52-1.03, P=0.068). All stratified groups could prognostically benefit from chemotherapy (low-risk group: HR 0.50, 95% CI 0.35-0.69, P<0.0001; intermediate-risk group: HR 0.34, 95% CI 0.26-0.44, P<0.0001; and high-risk group: HR 0.16, 95% CI 0.10-0.25, P<0.0001). Conclusion: A predictive nomogram and risk stratification model were constructed to assess prognosis in TNBC patients with de novo distant metastasis; these methods may provide additional introspection, integration and improvement for therapeutic decisions and further studies.